Self-study on Diligence as a Continuous Professional Development: A Teacher Researcher’s Perspectives - Dhungana, Parbati (Mangal Research Journal, 2021)
Nepali teachers’ professional qualities are discussed from non-socio-cultural perspectives, which seem insufficient for the continuous professional development of Nepali university teachers. Teachers’ professional attributes that influence their professional and pedagogical practices are rarely researched, particularly in Nepal. The purpose of this self-study was to investigate how I, a university teacher, could improve my pedagogical practices to facilitate a Research Methodology course for Science, Technology, Engineering, Arts and Mathematics (STEAM) graduates. Adapting a socio-cultural perspective, I purposefully asked myself and my 27 graduate students whom I taught in 2021 from August to October. I collected and analyzed information adapting dialogue as a research method. Making dialogues with myself and my students, I unveiled five ways of improving my pedagogical practices. They were: by (1) creating a supportive learning environment, (2) enhancing curiosity, (3) enhancing inquiry skills, (4) enhancing evaluation skills, and (5) developing continuous learning habits. My reflective journal, classroom discussions, activities, and assignments hold evidence of my improved pedagogical practices. Finally, I learnt that my enhanced diligence contributed to my learning and my student’s learning as my professional development.